G418 The clinical spectrum of dorsal stream dysfunction in autism – a retrospective cohort study of 13 children. (12th March 2018) - Hay, IJN; Assheton, D; Biggar, S; Ibrahim, H; Dutton, GN
Abstract : Aims: Bilateral dysfunction of the parieto-occipital cortex, linked to the visual cortex by the dorsal stream, variably produces simultanagnosia (SIM), optic ataxia (OA), and gaze apraxia. This triad, rarely reported in childhood, comprises 'Balint syndrome'. 'Dorsal stream dysfunction' (DSD) describes milder degrees of this disorder. This study aimed to determine the character and severity of DSD in a cohort of autistic children and to identify possible prognostic indicators for targeting specialist support. Methods: 13 able children with autism, sequentially receiving a tertiary neuro-ophthalmic diagnosis of DSD, were followed up over 6 years. Records were retrospectively reviewed for neurodevelopmental and neuro-ophthalmic examination results. Age-inappropriate configural disruption of elements of drawings was identified in the Beery-VMI Test of Visual-Motor Integration (VMI) as evidence of SIM and standard VMI scores (VMIS) were used to measure the severity of SIM. Still-frame analysis of video was used to confirm diagnoses of OA using the criterion of impaired terminal grip size relative to the target grasped. Severity of visual functional impairment was rated on mean individual Cerebral Visual Impairment Inventory scores (MCVIS) using as reference the 90th percentile cut-off MCVIS of 0.74 for the typically developing population. Correlation between MCVIS and VMIS was determined by linear regression analysis. Method agreement analysis for OA in central vision and motor coordination impairment (MCI), measured by the Beery Motor Coordination assessment, was determined by Cohen's weighted Kappa statistic (K). Results: Significant correlation was found between MCVIS and VMIS: r= −0.77 [95%CI: −0.93 to −0.83], p= 0.002 . Five children required specialist visual impairment (VI) support. The MCVIS for this group (3.05) differed significantly from the MCVIS for the non-support group (1.91) [difference 95% CI 0.74–1.55], p< 0.0001 . Agreement for severe MCI (≤5 th percentile) with central OA was significant: K=1 [95% CI: 0.46 to 1.54], p= 0.0002 . Conclusions: SIM may account for the visual perceptual impairment seen in ASD and OA may underpin motor impairment. MCVIS and VMIS may be useful indicators of the need for specialist VI support.